Rheological deformation and failure laws of boreholes in granite under thermo-mechanical coupling and its application in deep hole drilling of hot dry rock for geothermal energy exploitation. Issue 3 (October 2020) - Xi, Baoping; He, Shuixin; Wu, Yangchun; Chen, Zepeng; Cui, Jiming
Abstract: The key technology issue in deep hole drilling of hot dry rock (HDR) for geothermal energy exploitation is the stability of the surrounding rock. The temperature and in situ stress of the borehole play a significant role in its deformation and instability under high-pressure and high-temperature conditions. Based on the occurrence conditions of the granite reservoir of the Yangbajing geothermal field in Tibet, a research was conducted by means of experimental study, numerical simulation, and theoretical analysis, from which the following conclusions were drawn. (1) The deformation and failure laws of borehole are based on the physical experiment on granite specimen under high-temperature and high-pressure conditions. (2) The Weibull distribution of the thermal expansion coefficient is used for establishing rock heterogeneity, and the COMSOL software is used to reproduce the temperature and stress distribution of the borehole during physical experiment, thus demonstrating the distribution of the temperature field, stress field, and displacement field under thermo-mechanical coupling (TMC) condition. (3) Based on the complete analysis of the temperature field and stress field, combined with the conclusions of the deformation and failure of granite specimen under high-temperature and high-pressure conditions, the failure laws of borehole under the TMC condition were analyzed, as well as the critical conditions of borehole instability during deep hole drilling of HDR. (4) With the critical conditions of borehole instability during deep hole drilling of HDR, which the relation between the in situ stress σ and temperature T is σ = 241.9–0.3998 T. These conclusions have practical guiding significance to the stability control of the surrounding rocks of borehole in relation to projects such as geothermal energy exploitation from HDR, deep oil and gas resource extraction, and deep hole drilling in mainland China.